2010
DOI: 10.1007/s00122-010-1404-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-environment QTL mapping in blackcurrant (Ribes nigrum L.) using mixed models

Abstract: The first genetic linkage map of blackcurrant, published by Brennan et al. (Euphytica 161:19-34, 2008), identified regions where quantitative trait loci (QTLs) for some important traits were located. The analysis was complicated by the fact that the mapping population was found to contain two subgroups, with segregation ratios consistent with these being crossed and selfed offspring. The QTL analysis was based on the trait mean over 3 years and focused on the crossed offspring. Here we proposed a mixed model m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Thus, the growing conditions and microclimate have a larger effect on AsA content in 'Intercontinental' than in 'Titania'. Some researchers suggest that, although ascorbic acid content depends on the genotype, significant environmental effects have been noted in the level of ascorbic acid (Hancock et al, 2007;Pedersen, 2008;Brennan, Graham, 2009;Hackett et al, 2010). Our study revealed a strong negative correlation (r = −0.95) between average temperature in July and ascorbic acid content in the fruit.…”
Section: Genotype and Microclimate Conditions Influence Ripening Pattsupporting
confidence: 50%
“…Thus, the growing conditions and microclimate have a larger effect on AsA content in 'Intercontinental' than in 'Titania'. Some researchers suggest that, although ascorbic acid content depends on the genotype, significant environmental effects have been noted in the level of ascorbic acid (Hancock et al, 2007;Pedersen, 2008;Brennan, Graham, 2009;Hackett et al, 2010). Our study revealed a strong negative correlation (r = −0.95) between average temperature in July and ascorbic acid content in the fruit.…”
Section: Genotype and Microclimate Conditions Influence Ripening Pattsupporting
confidence: 50%
“…In 2003, the LOD score for budbreak in this region was less than the usual threshold of 3.0, but the QTL effect was the same sign [ 15 ]. A more powerful QTL by environment (year) analysis of the combined 2003 and 2004 data [ 23 ] showed that SERB09L03 ( GT022654 ) and SERB03C05 ( GT027101 ) were significantly associated with budbreak (p-value < 0.001) and that there was no significant QTL by year interaction. The mean budbreak for the heterozygous genotype at these SNPs was 4.0 days (se 2.35) earlier than the homozygote in 2002 and 1.6 (se 0.84) earlier in 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have focused on the genetic bases of phenolic compounds . Anthocyanins have been particularly well studied in fruits since they are major contributors to fruit quality . A cluster of three MYB genes involved in the anthocyanin content was identified following a quantitative trait locus (QTL) study on grape .…”
Section: Introductionmentioning
confidence: 99%